Knee pain in adults from the northeast of São Paulo, Brazil: prevalence, risk factors, and impact on quality of life - Alberto de Vitta; Nicoly Machado Maciel; Sandra Fiorelli Almeida Penteado Simeão; Matias Noll (ABCS Health Sciences)
Introduction: The existing literature describes several risk factors associated with knee pain, including personal, psychological, and work-related factors, among others. Furthermore, several studies have shown the negative impact of knee pain on quality of life; however, there is a lack of knowledge about knee pain in Latin American populations. Objective: This study aims to investigate the prevalence, risk factors, and impact on the quality of life of knee pain in Brazilian adults. Methods: This cross-sectional study was based on a population survey with 600 individuals interviewed using questionnaires including a) sociodemographic and labor aspects; b) physical activity level (IPAC questionnaire); c) musculoskeletal symptoms (Nordic questionnaire); and d) quality of life (SF-36). Results: The prevalence of knee pain was 25.6% (95% confidence interval: 22.3–29.3%), and it was associated with being >60 years old, black ethnicity, mean or low income, overweight, depression, gastrointestinal and renal diseases, and persons who performed occupations requiring repetitive movements, sitting while using a computer, and standing. All individuals with knee pain demonstrated significantly greater risks for summaries of the physical components. Conclusion: Knee pain is associated with socioeconomic variables, work aspects, and lifestyle factors and impacts the quality of life.